Multiple porcine circovirus 2-associated abortions and reproductive failure in a multisite swine production unit. - O'Connor, B (2001)
Porcine circovirus type 2 was detected in several stillborn and nonviable neonatal piglets presenting with chronic passive congestion, cardiac hypertrophy, and severe diffuse myocarditis. The presence of the virus in the heart and other tissues of affected piglets was confirmed by polymerase chain reaction, immunohistochemistry, and virus isolation techniques. Other reproductive losses and associated infectious agents in the herd are discussed.